THE IMPACT OF GOLD PRICE FLUCTUATIONS ON OPERATIONAL EFFICIENCY AND PROFITABILITY OF PT ANEKA TAMBANG TBK (ANTM): AN ANALYSIS BASED ON INVENTORY TURNOVER, RECEIVABLES TURNOVER, AND NET PROFIT MARGIN (2020–2024) - Haris, Abdul (Accounting Studies and Tax Journal (COUNT), 2025)
This study aims to analyze the impact of gold price fluctuations on the operational efficiency and profitability of PT Aneka Tambang Tbk (ANTM) during the period 2020–2024. Using a descriptive approach, the research examines the patterns of change in Inventory Turnover (IT), Receivables Turnover (RT), and Net Profit Margin (NPM) as key indicators of operational performance. The data show that the surge in gold prices in 2020 had a positive impact on the efficiency of inventory and receivables management, as well as an increase in net profit margin. Conversely, the decline in gold prices in 2021–2022 posed challenges for ANTM in maintaining financial performance stability. However, the company was able to adapt through more effective credit and operational management. These findings provide strategic insights for designing risk mitigation policies amidst global market volatility.